TELAAH KRITIS STATUS BADAN HUKUM DAN KONSEP DASAR BADAN USAHA MILIK DESA - Detania Sukarja; Mahmul Siregar; Tri Murti Lubis (Arena Hukum, 2020)
Abstract Law No. 6 of 2014 on Villages (Village Law) appears to construct Village-Owned Enterprise or Badan Usaha Milik Desa (BUM Desa) as a new form of business entity within the Indonesian legal sphere. BUM Desa is considered to be different from other variants of business entities in Indonesia. There are multiple interpretations regarding the status of BUM Desa, debating whether they are legal entities or not. This normative legal research discusses the legal aspects of BUM Desa following the promulgation of the Village Law. It concludes that: (1) theoretically BUM Desa meets the criteria as a public legal entity. The issuance of Law No.11 of 2020 on Job Creation confirms the status of BUM Desa as a legal entity; (2) BUM Desa is a public business entity with a unique character to villages different from other forms of business entity with private ownership such as limited companies and cooperatives. However, legal provisions on BUM Desa still contain logical inconsistencies regarding the basic conception of BUM Desa and Law 12/2011 does not yet include Perdes as statutory regulation. The confirmation of the status of BUM Desa legal entities needs to be complemented by synchronization with Law 12/2011 to strengthen the position of Perdes as the legal basis for the establishment of BUM Desa along with various other sectoral regulations Abstrak Â Undang-Undang Nomor 6 Tahun 2014 tentang Desa (â€œUU Desaâ€) terkesan mengkonstruksikan Badan Usaha Milik Desa (BUM Desa) sebagai suatu bentuk badan usaha baru dalam ranah hukum Indonesia. BUM Desa dianggap tidak sama dengan varian badan usaha lain yang ada di Indonesia. Timbul multitafsir mengenai status BUM Desa, apakah berbadan hukum atau tidak berbadan hukum. Penelian hukum normative ini membahas aspek hukum BUM Desa pasca diundangkannya UU Desa. Hasilnya (1) secara teoritis BUM Desa memenuhi kriteria sebagai badan hukum public. Lahirnya UU Cipta Kerja menegaskan status BUM Desa sebagai badan hukum; (2) BUM Desa adalah badan usaha publik bercirikan Desa yang berbeda dengan bentuk-bentuk badan usaha lainnya dimana terdapat kepemilikan privat seperti PT dan koperasi. Namun, ketentuan terkait BUM Desa masih memuat inkonsistensi nalar mengenai konsepsi dasar BUM Desa dan UU 12/2011 tidak mencantumkan Perdes dalam tata urutan peraturan perundang-undangan. Penegasan status badan hukum BUM Desa perlu dilengkapi dengan sinkronisasi dengan UU 12/2011 untuk memperkuat kedudukan Perdes sebagai dasar hukum pendirian BUM Desa dan juga dengan berbagai peraturan sektoral lainnya.